Identification of MicroRNAs in the West Nile Virus Vector Culex tarsalis (Diptera: Culicidae). Issue 2 (7th December 2022) - Asad, Sultan; Mehdi, Ahmed M; Pujhari, Sujit; Rückert, Claudia; Ebel, Gregory D; Rasgon, Jason L
Abstract: MicroRNAs (miRNAs) are a group of small noncoding RNAs that regulate gene expression during important biological processes including development and pathogen defense in most living organisms. Presently, no miRNAs have been identified in the mosquito Culex tarsalis (Diptera: Culicidae), one of the most important vectors of West Nile virus (WNV) in North America. We used small RNA sequencing data and in vitro and in vivo experiments to identify and validate a repertoire of miRNAs in Cx. tarsalis mosquitoes. Using bioinformatic approaches we analyzed small RNA sequences from the Cx . tarsalis CT embryonic cell line to discover orthologs for 86 miRNAs. Consistent with other mosquitoes such as Aedes albopictus and Culex quinquefasciatus, miR-184 was found to be the most abundant miRNA in Cx. tarsalis . We also identified 20 novel miRNAs from the recently sequenced Cx. tarsalis genome, for a total of 106 miRNAs identified in this study. The presence of selected miRNAs was biologically validated in both the CT cell line and in adult Cx. tarsalis mosquitoes using RT–qPCR and sequencing. These results will open new avenues of research into the role of miRNAs in Cx. tarsalis biology, including development, metabolism, immunity, and pathogen infection.